DEVELOPMENT OF HOSPITAL RESERVATION INFORMATION SYSTEM WITH UDC METHOD AND SUS TESTING - Kurniawan, Adrian; Saputra, Candra Eka; Aldo, Dasril (Universitas Trilogi, 2023)
Information system is a system that combines technology used to help human life. Not only helps facilitate information sistem activities, it also saves time, space and costs. Utilization of a website is useful in all fields because there are many and very broad and user-friendly features that can spoil the user's eyes. Activities that function to meet the needs of the general public are the meaning of public services as well as those related to other commodities such as goods, services and management provided by the organizers. In the health sector in public services, it is very necessary, especially in the service reservation process which still uses a queuing sistem in the form of taking queue numbers in the hospital lobby and waiting for hours, causing queues of visitors. The purpose of this study was to design a reservation information system at the hospital in order to increase the use of facilities and resources. The design of this hospital reservation information system is based on a website that was built using the user centered design method and tested using the SUS (Sistem Usability Scale) method which is in accordance with the criteria for the Sistem Usability Scale method which involves several respondents for information system acceptance